Methodological proposal to analyze restaurant menus based on the Arthur D. Little Matrix - Riquelme Barros, Rodrigo E. (2020)
Menu engineering is a set of key tools to evaluate the restaurant menu. For a long time it was thought that the Boston Consulting Group (BCG) Matrix was the only tool to enable to do this evaluation; butthere are other instruments that help analyze the permanence or removal of dishes in the menu. So far, in addition to the BCG Matrix, we can use the following tools: Cost engineering (Omnes principles), profitability index per dish (PID), popularity index, Pavesic Matrix, Miller Matrix, and the multi-criteria analysis. In this article, we propose to use the Arthur D. Little (ADL) Matrix as it complements the analysis of the restaurant menus by observing two complementary concepts: the amounts sold and the product shelf life (contribution margin). In order for the ADL matrix to contribute to menu engineering, we propose to re-structure this matrix with the explanation and results obtained so as to have better tools at the time of deciding the distribution, selection, permanence or removal of dishes in the menu.